Sistema de reprodução, parentesco e tamanho efetivo em sementes de polinização livre de populações fragmentadas de Copaifera langsdorffii Desf. por análise de locos microssatélites - Manoel, Ricardo de Oliveira [UNESP] (2012)
Anthropogenic changes in the reproductive population density can affect the mating system and result in an increase in selfing and correlated matings. This study investigated the mating system in small fragmented populations of the insect pollinated tropical tree species Copaifera langsdorffii, using microsatellite loci and the mixed and correlated mating models. Open-pollinated seeds were collected from 15 seed-trees located in a small forest fragment (4.8 ha), denominated Bosque and from 14 other seed-trees located in other small forest fragments of the north-western region of São Paulo State. No significant differences were observed between the seed-trees from Bosque (tm=0.933±0.028) and other fragments (tm=0.971±0.032), although these estimates were significantly different from 1.0, suggesting that selfing was occurring. Differences between multilocus and unilocus outcrossing rate were significantly high in both seed-trees of Bosque (tm -ts=0.478±0.05) and other forest fragments (tm -ts=0.475±0.018), suggesting a spatial genetic structure in those stands. The results also showed high rates of correlated mating in the samples, indicating that a good part of the offspring were full-sibs. As a consequence of selfing, mating among relatives and correlated matings, the coancestry within families was equally high in the seed-trees of Bosque ((Θ=0.237) and in the seed-trees of the other forest fragments (Θ=0.241) and the effective population size was lower than expected in panmitic populations (Ne<4). The results were discussed, focusing on the sample size of seed-trees to collect seeds for genetic conservation and enviromental reforestation.